Bacteriological and Physical Quality of Locally Packaged Drinking Water in Kampala, Uganda - Halage, Abdullah Ali (Hindawi Publishing Corporation, 2015)
Objective. To assess the bacteriological and physical quality of locally packaged drinking water sold for public consumption. Methods. This was cross-sectional study where a total of 60 samples of bottled water from 10 brands and 30 samples of sachet water from 15 brands purchased randomly were analyzed for bacteriological contamination (total coliform and faecal coliform per 100 mL) using membrane filtrate method and reported in terms of cfu/100 mL. Results. Both bottled water and sachet water were not contaminated with faecal coliform. Majority (70%, 21/30) of the sachet water analyzed exceeded acceptable limits of 0 total coliforms per 100 mL set by WHO and the national drinking water standards. The physical quality (turbidity and pH) of all the packaged water brands analyzed was within the acceptable limits. There was statistically significant difference between the median count of total coliform in both sachet water and bottled water brands (U(24) = 37.0, p = 0.027). Conclusion. Both bottled water and sachet water were not contaminated with faecal coliforms; majority of sachet water was contaminated with total coliform above acceptable limits. Government and other stakeholders should consider intensifying surveillance activities and enforcing strict hygienic measures in this rapidly expanding industry to improve packaged water quality.